2015
DOI: 10.1016/j.aorn.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Costs of Reconciling Surgical Sponge Counts

Abstract: Retained surgical sponges are serious adverse events that can result in negative patient outcomes. The primary method of prevention is the sponge count. Searching for sponges to reconcile counts can result in inefficient use of OR time. The purpose of this descriptive study was to estimate the cost of nonproductive OR time (ie, time spent not moving forward with the surgical procedure) spent reconciling surgical sponge counts and the cost of using radiography to rule out the presence of retained sponges. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Therefore, we need to acknowledge that surgical counting is a complex process that should be respected as part of the surgical procedure rather than undertaking the effort to educate ORT in terms of counting surgical material on a redundant base. Additionally, ensuring flawless counting with no interruption during the process itself might save a significant amount of hidden costs which could be an even bigger argument for cost efficiency centered perspectives …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we need to acknowledge that surgical counting is a complex process that should be respected as part of the surgical procedure rather than undertaking the effort to educate ORT in terms of counting surgical material on a redundant base. Additionally, ensuring flawless counting with no interruption during the process itself might save a significant amount of hidden costs which could be an even bigger argument for cost efficiency centered perspectives …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ensuring flawless counting with no interruption during the process itself might save a significant amount of hidden costs which could be an even bigger argument for cost efficiency centered perspectives. 15,16 That RSM is impossible to be ruled out completely was shown by Inaba et al 1 They presented during a convincing trial that during 2051 emergency operations involving emergency cavitary surgery, a total of 11 left surgical sponges were detected using a radio frequency detector even though all checklists were fulfilled correctly.…”
Section: Discussionmentioning
confidence: 99%
“…Reconciling a sponge count often requires searching for sponges in the patient and OR environment. In one academic hospital, the time spent searching for sponges to reconcile the sponge count ranged from 1 minute to 90 minutes per procedure . The annualized time spent searching for surgical sponges was found to be more than 2,266 minutes, and using radiography to rule out a retained sponge required an additional 2,080 minutes .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among the three surgical items researched in the present study, the counting of sponges was the procedure that was most often carried out in the operation room. It is worth mentioning that among the surgical items retained, sponges are the most common (8,(20)(21) . As already mentioned, most participants reported that the circulating technician was the person responsible for counting sponges, and that the procedure was carried out at different times, but always ended before surgical synthesis.…”
Section: Variablesmentioning
confidence: 99%
“…In a descriptive study, the authors asked perioperative nurses (n=3,137) for a list of priority topics for patient safety, and the ten topics most often reported, the prevention of retention of surgical items was in the second position, that is, 61% of the professionals identified this topic as high priority (6) . Currently, there are advances in the prevention of retention of surgical items; however, it is still an adverse event that occurs in operation rooms, causing physical, emotional, and financial damages for patients, in addition to increasing costs for healthcare services (7)(8) .…”
Section: Introductionmentioning
confidence: 99%